Optimizing the Traditional Agroforestry System (Dusung) of the Airlouw Community: Review of Ecology and Productivity of Food Commodities - Noviar Flasiana Wenno; Simon Matakena (Jurnal Penelitian Pendidikan IPA, 2025)
This study investigates the traditional Dusung agroforestry system of the Airlouw Hamlet community in Nusaniwe District, Ambon City, focusing on its ecology and productivity as a sustainable source of food commodities. The research employs a review of the Dusung system's capacity to meet the daily subsistence needs of the local community through its regular and continuous management. Data were collected using a census of 30 Dusung managers, incorporating both primary data (direct observation and interviews) and secondary sources (literature and existing reports). Analysis was conducted descriptively using both quantitative (productivity metrics) and qualitative (management practices) methods. The findings indicate that the high productivity and yield potential of the Dusung system are critically dependent on the optimal ecological management practices implemented by the farmers. The traditional system, characterized by a mix of agricultural commodities and livestock integration, functions as a primary source of food for the Airlouw community. However, the study reveals that the size of the Dusung plot does not linearly correlate with the actual commodity yield. Therefore, optimizing the system hinges on enhancing management strategies rather than merely expanding land area.